If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1b + -3) = 72 Reorder the terms: 4(-3 + 1b) = 72 (-3 * 4 + 1b * 4) = 72 (-12 + 4b) = 72 Solving -12 + 4b = 72 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4b = 72 + 12 Combine like terms: -12 + 12 = 0 0 + 4b = 72 + 12 4b = 72 + 12 Combine like terms: 72 + 12 = 84 4b = 84 Divide each side by '4'. b = 21 Simplifying b = 21
| 21/10n=1/6 | | y^3-6=3 | | (4x)/3-2=2x | | 6x+3y-4(6x-7y)= | | 63/5-21/4 | | -6z/8+7/8=6z/5-11/5-2z/3 | | 7/3x+1/3x=2x+3/3+5/3x | | x^3+2x^2+8x+8=0 | | 2x/3-2/3=-7x/2+4x/3 | | 15.96+2s=T | | y=-3x-69 | | (x+10)/2=7(x-1) | | T=2s+25.96 | | x+2y=-18 | | .5q=315 | | -2=-2(3x-5) | | 1.9y-1.6y= | | -2x-3y=1 | | 5q=315 | | y^11+6=-7 | | 2+2x=4x-8 | | -4x-12y=36 | | y^3+5=-7 | | -16t^2-11t+150=0 | | 3x-12y=27 | | -5(-3q+11)+4(-1-5q)= | | -8p-2p=3+1-6p-5p | | 9n^2-3n=2 | | 3y+3x=36 | | 64n^2=49 | | 5n^2=20n | | 5x^2-1=3 |